Strengthening our professional identity: Insights from the 2017 ACHEO conference - Orsini, Cesar (Journal of Oral Research, 2019)
Earlier this year, on April 21st and 22nd, over 320 members of the dental education community, including educators, clinicians, researchers, students, and academic and professional policy makers, convened at the Faculty of Dentistry of the University San Sebastian in Santiago, Chile, for the second ACHEO conference (ACHEO as acronym for Asociación Chilena de Enseñanza de la Odontología, Association for Dental Education in Chile). This twoday meeting was co-hosted by ACHEO and the Faculty of Dentistry of the University San Sebastian, and co-sponsored by the thirteen active ACHEO member Faculties of Dentistry.